Terapi Aktifitas Kelompok (TAK): Stimulasi Persepsi Modifikasi sebagai Alternatif Pengendalian Halusinasi Dengar pada Klien Skizofrenia - Ah. Ah. Yusuf; Rizki Fitryasari; Nursalam Nursalam; Iskandar Iskandar (Universitas Airlangga, 2007)
The objective of this study was to examine the effect of modified Group Activity Therapy (GAT) perception stimulation on auditory halucination controlling in schizophrenia. Modification means using only 3 sessions in GAT. A quasi-experimental pre post test design was used in this study. Eighteen samples with auditory halucination at male third’s class wards Menur Mental Hospital Surabaya were used in this study and divided into 2 groups. Observation was applied to measure patient’s responses and data were analyzed by Wilcoxon Signed Rank test and Mann Whitney test with significance level of α<0.05.Conclusion: modified perception stimulation of GAT is able to increase patient’s ability for making differences between reality and non-reality and motivated patient to choose and use the best way for controlling halucination.